Numerical simulation on the effect of anastomosis and stenosis upon radiocephalic arteriovenous fistula - Wan Anuar Wan Hassan, 1985-, author; Kahar Osman, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014